The effect of web-based Thai language learning site on recalling performance and motivation among undergraduate students - Suriani, Sukri; Sharifah Raudzah, S. Mahadi; Zarina, Samsudin, Assoc. Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.